Economics of vertical restraints for multi-sided platforms - Evans, David S. 1954- (2013)
"This paper presents an overview of what economists can say about vertical constraints by multi-sided platforms at this stage in the development of our knowledge about the economics of these businesses. It describes the general procompetitive and anticompetitive uses of vertical restraints by multi-sided platforms. It then focuses on the role of critical mass for multi-sided platforms and how vertical restraints might be used on the one hand, anti-competitively to prevent rivals from achieving critical mass and long-term growth and, on the other hand, pro-competitively, to ensure the platform and its customers that the platform will remain viable."